2018
DOI: 10.1158/1078-0432.ccr-18-0532
|View full text |Cite|
|
Sign up to set email alerts
|

RAB37 Hypermethylation Regulates Metastasis and Resistance to Docetaxel-Based Induction Chemotherapy in Nasopharyngeal Carcinoma

Abstract: Epigenetic alterations play important roles in metastasis and drug resistance through gene regulation. However, the functional features and molecular mechanisms of epigenetic changes remain largely unclear in nasopharyngeal carcinoma (NPC) metastasis. Gene regulatory network analysis was used to identify metastatic-specific dysregulated genes between normal and NPC tissues and the expression was validated in published Gene-Expression Omnibus data set. The regulatory and functional role of downregulation was ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Methylation modification plays an important role in NPC metastasis, but the mechanisms remain poorly understood. We have previously reported that hypermethylation of the HOPX, RAB37, and SHISA3 genes might serve as molecular biomarkers to predict NPC metastasis [17,26,27]. Therefore, the mechanisms and significance of methylation regulation in NPC are worthy to be study in greater detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation modification plays an important role in NPC metastasis, but the mechanisms remain poorly understood. We have previously reported that hypermethylation of the HOPX, RAB37, and SHISA3 genes might serve as molecular biomarkers to predict NPC metastasis [17,26,27]. Therefore, the mechanisms and significance of methylation regulation in NPC are worthy to be study in greater detail.…”
Section: Discussionmentioning
confidence: 99%
“…Six NPC cell lines (CNE2, SUNE1, HONE1, HNE1, 5-8F, and 6-10B) were cultured in RPMI-1640 (Invitrogen, Carlsbad, CA, USA) supplemented with 10% FBS (ExCell Bio, Shanghai, China), and two normal nasopharyngeal epithelial cell lines (NP69 and N2-Tert) were grown in KSFM (Invitrogen) supplemented with bovine pituitary extract (BD Biosciences, Franklin Lake, NJ, USA). NP69, N2-Tert and all NPC cell lines had been authenticated and were gifts from Dr. Mu-sheng Zeng (Sun Yat-sen University Cancer Center, China) [17,18]. HEK293T cells were grown in DMEM supplemented with 10% FBS, and were obtained from ATCC.…”
Section: Clinical Specimens and Cell Culturementioning
confidence: 99%
“…On the other hand, TIMPs inhibited tumor invasion and metastasis [101]. TIMP-2 upregulation was linked to metastasis via MMP-2 inactivation in nasopharyngeal carcinoma [102]. Additionally, a high ratio of MMP-9 to TIMP-2, implicating that a higher TIMP-2 level leads to drug resistance, was beneficial for the treatment of metastatic renal cell carcinoma [103].…”
Section: Expression Of Mmps and Timps In Rb Cellsmentioning
confidence: 99%
“…MMP2 is mediated by NF-κB [28], and MMP2/9 is involved in the ERK1/2-MMP2/9 extracellular signalregulated kinase signalling pathway [29]. Tissue inhibitor of metalloproteinase-2 (TIMP2) is an upstream gene of MMP2 [30], and the imbalance of MMP2/TIMP2 may have prognostic value for nasopharyngeal carcinoma. e results of immunohistochemistry analysis showed that the proportion of cells stained positive for TIMP2 in NPC was significantly higher than that in inflammatory tissues, and the proportion of positive cells increased significantly with lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%